Indirect Information Transfer: Three‐Spined Sticklebacks Use Visual Alarm Cues From Frightened Conspecifics About an Unseen Predator. (2nd September 2013) - Hogan, Kelly E.; Laskowski, Kate L.
Abstract: Animals can attempt to reduce uncertainty about their environment by gathering information personally or by observing others' interactions with the environment. There are several sensory modalities that can be used to transmit social information from chemical to visual to audible cues. When predation risk is variable, visual cues of conspecific behavior might be especially telling about the presence of a potential threat; however, most studies couple visual and chemical cues together. Here, we tested whether visual behavioral cues from frightened conspecifics were sufficient to indirectly transfer information about the presence of an unseen predator in three‐spined sticklebacks. Our results demonstrate that visual behavioral cues from conspecifics about the presence of a predator are sufficient to induce an antipredator response. This suggests that information transfer can occur rapidly in the absence of chemical cues and that some individuals weigh social information more heavily than others.